Predictors of response to exercise training in patients with coronary artery disease – a subanalysis of the SAINTEX-CAD study. (29th August 2020) - Witvrouwen, Isabel; Pattyn, Nele; Gevaert, Andreas B; Possemiers, Nadine; Van Craenenbroeck, Amaryllis H; Cornelissen, Veronique A; Beckers, Paul J; Vanhees, Luc; Van Craenenbroeck, Emeline M
Abstract: Exercise training improves peak oxygen uptake, an important predictor of mortality in coronary artery disease patients. The influence of clinical and disease characteristics on training response is not well established in coronary artery disease. Therefore, we aimed to evaluate whether baseline cardiovascular disease variables and training intensity can predict the maximal aerobic response to exercise training. The Study on Aerobic INTerval EXercise training in coronary artery disease patients (SAINTEX-CAD) previously showed that 12 weeks of aerobic interval training and continuous training equally improved peak oxygen uptake in coronary artery disease patients. We identified 24 exercise non-responders (change peak oxygen uptake <1 ml/kg/min) among 167 participants in SAINTEX-CAD. In a between-group comparison, exercise non-responders were older, their baseline peak oxygen uptake and oxygen uptake efficiency slope were higher, and exercise non-responders were more frequently included after elective percutaneous coronary intervention (all p < 0.05). In multiple logistic regression analysis, age (odds ratio = 1.11 (1.04–1.18), p = 0.001), history of elective percutaneous coronary intervention (odds ratio = 3.31 (1.12–9.76), p = 0.030) and higher baseline peak oxygen uptake (odds ratio = 1.16 (1.06–1.27), p = 0.001) were independent predictors of exercise non-response. In multiple linear regression analysis, age (ß = −0.605, p = 0.001), history of elective percutaneous coronary intervention (ß = −15.401, p = 0.010), training intensity (ß=0.447, p = 0.008), baseline physical activity (ß=0.014, p = 0.003) and oxygen uptake efficiency slope (ß = −0.014, p < 0.001) predicted percentage change in peak oxygen uptake and explained 41% of the variability in percentage change in peak oxygen uptake. To summarize, 14% of coronary artery disease patients were exercise non-responders. Higher baseline peak oxygen uptake and oxygen uptake efficiency slope, history of elective percutaneous coronary intervention, older age, lower training intensity and lower baseline physical activity were predictors of training non-response. Identification of patients with a large likelihood of non-response is a first step towards patient tailored exercise programmes.